Philip A. Cunningham, Joseph Sievers, Mary Boys, Hans Herman Henrix, and Jesper Svartik, Eds. Christ Jesus and the Jewish People Today: New Explorations of Theological Interrelationships - Korn, Eugene (Studies in Christian-Jewish Relations, 2013)
No abstract is available.